Biosocial risk factors for academic dishonesty : testing a new mediation model in young adults - Portnoy, Jill (2020)
Researchers increasingly recognize that biological risk factors contribute to the development of antisocial behavior. Although academic dishonesty is a pervasive problem, this type of antisocial behavior has not been investigated in biosocial research. This article addresses this limitation by examining the relationship between academic dishonesty and resting heart rate in a sample of undergraduates (N = 149, 65.69% female, M age = 19.62 years). Subjects completed self-report academic dishonesty questionnaires, and heart rate was measured during a resting period. Low resting heart rate was associated with more frequent and varied academic dishonesty in females, but not in males. Self-control and sensation seeking, but not fearlessness, mediated this relationship in females. To our knowledge, this is the first study to examine a biological risk factor for academic dishonesty. This is also the first study to examine self-control as a possible mediator of the resting heart rate–antisocial behavior relationship in adults. Findings suggest a potential pathway in young adults through which low resting heart rate may affect antisocial behavior.